Optimisation of trimethylolpropane ester synthesis from waste cooking oil methyl ester by response surface methodology, and its physicochemical properties and tribological characteristics - Teuku Meurah Indra Riayatsyah; Arridina Susan Silitonga; Md Abul Kalam; Islam Md Rizwanul Fattah (Results in Engineering)
This study is focused on optimising the process variables of trimethylolpropane (TMP) ester synthesis from waste cooking oil methyl ester (WCOME) using response surface methodology with Box–Behnken experimental design in order to maximise the TMP ester (TWCOE biolubricant) yield. The following process variables were optimised: (1) reaction time, (2) TMP-to-WCOME ratio, and (3) sodium methoxide catalyst concentration. The predicted TWCOE biolubricant yield was 97.06 %, which conformed well with the experimental TWCOE biolubricant yield of 96.12 %. The quadratic response surface model demonstrated a robust fit with the experimental data (R² = 0.9888).The physicochemical properties and tribological characteristics of the TWCOE biolubricant were assessed and compared with those of commercial lubricants. The TWCOE biolubricant had a kinematic viscosity of 41.55 mm2/s at 40 °C and 6.93 mm2/s at 100 °C. The TWCOE biolubricant had an acid value of 0.4 mg KOH/g, flash point of 222.2 °C, and viscosity index of 125.30. The coefficient of friction of the TWCOE biolubricant (0.045) was lower than those of the SAE15W40, SAE0W30, and ATF9 lubricants (0.062, 0.088, and 0.089, respectively). However, the average wear scar diameter for the TWCOE lubricant (0.632 mm) was higher than those of commercial lubricants. The favourable lubricating characteristics suggest that the TWCOE biolubricant has the potential for use as an effective lubricant or additive in industrial machinery.